Surface Electromyography Normalization Affects the Interpretation of Muscle Activity and Coactivation in Children With Cerebral Palsy During Walking - Gagnat, Yngvild; Brændvik, Siri Merete; Roeleveld, Karin (Frontiers in Neurology, 2020)
Investigating muscle activity and co-activation with surface electromyography (sEMG) gives insight into pathological muscle function during activities like walking in people with neuromuscular impairments, as children with cerebral palsy (CP). There is large variation in the amount of co-activation reported during walking in children with CP, possibly due to the inconsistent handling of sEMG and in calculating the co-activation index. The aim of this study was to evaluate how different approaches of handling sEMG may affect the interpretation of muscle activity and co-activation, by looking at both absolute and normalised sEMG. Twenty-three ambulatory children with CP and 11 typically developing children (TD) participated. They conducted a 3-dimensional gait analysis (3DGA) with concurrent sEMG measurements of tibialis anterior, soleus, gastrocnemius medialis, rectus femoris and hamstring medialis. They walked barefoot at a self-selected, comfortable speed back and forth a 7-m walkway. The gait cycle extracted from the 3DGA was divided into six phases, and for each phase root mean square sEMG amplitude was calculated (sEMG-abs). RMS was also normalised to peak amplitude of the linear envelope (50 ms running RMS window) during the gait cycle (sEMG-norm). The co-activation index was calculated using these two sEMG approaches and by using two different indices. Differences between TD children´s legs and the affected legs of children with CP were tested with a mixed model. The between-subject muscle activity variability was more evenly distributed using sEMG-norm, however, potential physiological variability was eliminated as a result of normalisation. Differences between groups in one gait phase using sEMG-abs showed opposite differences in another phase using sEMG-norm for three out of the five muscles investigated (decreased changed into increased and vice versa). Children with CP showed an increased co-activation index in two out of three muscle pairs using sEMG-abs, and in all three muscle pairs using sEMG-norm. These results were independent of index calculation method. Moreover, the increased co-activation index reported could be explained by either reduced agonist muscle activity or increased antagonist activity. Our results show that the normalisation approach should be taken into consideration, when interpreting muscle activity and the co-activation index.